Vous êtes sur la page 1sur 1

@ @bma@@pbba

V1
a f x0 :

4 x 2 3 x 27
= ) f ( x
1)
; x 0 =3
x3
f (3) = a

x +1 2
= ) f ( x
2)
; x0 = 1
x 1
f (1) = a

)2 tan( x) + sin( x

; x0 = 0
= ) f ( x
3)
x
f (0) = a

 V2
(1 100 :

12

; 80

; 13

; 15

; . 3 28

(2 :
2 1
2 +1

1
433

3) 3
4

2) 3

10 2 8 3
7
3

1
3
3 1

)1

1
)4
1+ 3 3 + 3 9

)5

5 4

 V3
x x 3 x3 + 6 x 7

x 1

f :x

+ . 1+

 V4
f x0 :
x + 1 1
; x0 = 0
x

x x+6
; x0 = 3
4x + 1 3

= )2) f ( x

x3a
= )4) f ( x
; x0 = a > 0
x a
3

 V5

x0 = 0

= )1) f ( x

)sin( x
3) f ( x) = 3
;
x + 1 1

:
x

12

x
x

4
3

x +1
x +1

x +1 1
x + 1 1
3

3) lim

x + 3

x 2 x + 1
3

2) lim
x 0

x 1

 6V
(1 a b ). x3 3x 18 = ( x 3)( x + ax + b
(2 . t = 3 9 + 4 5 + 3 9 4 5
3
(a t ) x3 3x 18 = 0 ) .( ( u + v ) = u 3 + v 3 + 3uv (u + v
(b . t=3

http://4maths.jimdo.com
Ali TAMOUSSIT

1) lim
x 1